2012
DOI: 10.5478/msl.2012.3.1.018
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Peptide-Ion Generation by Laser-Induced Surface Heating from Tungsten Silicide Surfaces

Abstract: We report observation of laser desorption/ionization (LDI) of peptides from flat surfaces of tungsten silicide (WSi 2 ). In contrast to MALDI (matrix-assisted laser desorption/ionization) and SALDI (surface-assisted laser desorption/ionization) mass spectrometry, this study did not utilize any matrices and surface nanostructures. In this work, LDI on WSi 2 surfaces is demonstrated to cover a mass range up to 1,600 Da (somatostatin; monoisotopic mass = 1637.9 Da). In addition, it exhibited a high sensitivity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Such rapid surface heating is known to promote the intact desorption of thermally labile molecules from the early field desorption mass spectrometry [12]. Very recently, the thermal aspect involved in the LDI process has been further supported by pronounced LDI of peptides from the flat surfaces of a-Si and WSi x [7,8]. The thermal properties of a-Si and WSi x , such as a very low thermal conductivity (K) and a very high heat capacity (C p ), respectively, make the surfaces to be amenable to laser-induced surface heating, which may replace the needs of the presence of surface nanostructures for LDI of thermally labile molecules from the surfaces.…”
Section: Ldi Of Peptides On Soi Wafers Via Laser-induced Surface Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such rapid surface heating is known to promote the intact desorption of thermally labile molecules from the early field desorption mass spectrometry [12]. Very recently, the thermal aspect involved in the LDI process has been further supported by pronounced LDI of peptides from the flat surfaces of a-Si and WSi x [7,8]. The thermal properties of a-Si and WSi x , such as a very low thermal conductivity (K) and a very high heat capacity (C p ), respectively, make the surfaces to be amenable to laser-induced surface heating, which may replace the needs of the presence of surface nanostructures for LDI of thermally labile molecules from the surfaces.…”
Section: Ldi Of Peptides On Soi Wafers Via Laser-induced Surface Heatingmentioning
confidence: 99%
“…For example, it was recently found that the flat surfaces of amorphous Si (a-Si) [7] and tungsten silicide (WSi x ) [8] yielded pronounced LDI of peptide molecules without assistance of surface nanostructures. As LDI on flat surfaces avoids the utilization of nanostructures that necessitates well-controlled surface fabrication, the use of flat surfaces makes it simpler, easier, and more reproducible to prepare uniform target surfaces.…”
mentioning
confidence: 99%
“…With the goal of optimizing MALDI-MS analysis, extensive efforts have been made to investigate matrix effect, 17,18 matrix additives, 19 sample-matrix preparation methods, [20][21][22] and its mechanism. [23][24][25][26] MALDI-TOF (time-of-flight) MS has become a standard analysis tool for the structural analysis of synthetic polymers. MALDI-TOF MS analysis of synthetic polymers readily provides polymer characteristic information such as the average molar mass (M W ), molar mass distribution (MMD), repeat unit structure, copolymer sequence, and the endgroup.…”
Section: Introductionmentioning
confidence: 99%